2023
DOI: 10.1017/s2045796023000161
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and mental health–related emergency department and hospital encounters among children, adolescents and young adults

Abstract: Aims We examine the association between high ambient temperature and acute mental health-related healthcare encounters in New York City for children, adolescents and young adults. Methods This case-crossover study included emergency department (ED) visits and hospital encounters with a primary diagnosis of any mental health disorder during warm-season months (June–August) in New York City from 2005 to 2011 from patients of three age groups (6–11, 12–17 and 18–25 years). Using a distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…More specifically for youths, Niu et al. ( 2023 ) found that high summer temperatures were associated with a significant increase in MBD‐related ER visits. However, in our analysis, we found that not only was maximum temperature normally not the most predictive variable, but a high maximum temperature resulted in lower MBD‐related hospital visits when it was a top contributing variable.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically for youths, Niu et al. ( 2023 ) found that high summer temperatures were associated with a significant increase in MBD‐related ER visits. However, in our analysis, we found that not only was maximum temperature normally not the most predictive variable, but a high maximum temperature resulted in lower MBD‐related hospital visits when it was a top contributing variable.…”
Section: Discussionmentioning
confidence: 99%
“…We modeled the non-linear effect of Tmin cumulatively over lag days 0–5 on injury-related ED visits. We chose this lag period based on our prior analyses of ambient temperature and ED visits, which explored varying lag structures and functional forms (Winquist et al 2016 , Sheffield et al 2018 , Niu et al 2023 ). These studies commonly examined a 6 d lag period (case day plus six lag days); prior results indicated significant effects of heat only on the case day (supplemental figure S5).…”
Section: Methodsmentioning
confidence: 99%
“…These studies commonly examined a 6 d lag period (case day plus six lag days); prior results indicated significant effects of heat only on the case day (supplemental figure S5). Consistent with previous research, the lag-response curve for Tmin was modeled as a cubic spline with 3 degrees of freedom, to account for the non-linear relationship between Tmin and injury-related ED visits (Niu et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%